Activities of the ECLAC system to promote and support South-South cooperation during the 2006-2007 biennium (ECLAC [Santiago]CL, 2008)
Contains the main data and a brief analysis of the ECLAC technical cooperation programmes, with special reference to the South-South component.
Keywords: ECLAC